2008
DOI: 10.1007/s11294-008-9188-1
|View full text |Cite
|
Sign up to set email alerts
|

Structural Change in Rural Croatia—Is Early Retirement An Option?

Abstract: Early retirement, Farm structures, Rural development, Croatia, Q12, Q18,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 17 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…The schemes were not continued in the 2024-2020 Common Agricultural Policy, because they were judged to be largely ineffective: several studies found that many beneficiaries would have retired anyway only few years later (e.g. Bika, 2007;Fellmann and Möllers, 2009). In France, this measure was replaced by a one-off early-retirement subsidy.…”
Section: Review Of Programmes To Support Young Farmersmentioning
confidence: 99%
“…The schemes were not continued in the 2024-2020 Common Agricultural Policy, because they were judged to be largely ineffective: several studies found that many beneficiaries would have retired anyway only few years later (e.g. Bika, 2007;Fellmann and Möllers, 2009). In France, this measure was replaced by a one-off early-retirement subsidy.…”
Section: Review Of Programmes To Support Young Farmersmentioning
confidence: 99%